Bimbingan Teknis Kelompok Penyelenggara Pemungutan Suara (KPPS) Desa Blorok Dalam Pemilihan Umum Tahun 2024 - Dendy Kurniawan; Nur Faizin; Ainul Maftuchah; Sunarto Sunarto; Anwar Anwar; Bagus Sembodo (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This community service aims to provide an understanding of technical instructions regarding the implementation of voting and vote counting for the voting organizer group in Blorok Village, Brangsong subdistrict, Kendal district in the 2024 general election. This technical guidance takes place in 2 sessions in one day. In the first session of this technical guidance activity, material was provided regarding preparations before carrying out voting. Then in the second session material was given about the implementation of voting, and in the third session material was given about vote counting and an introduction to the Sirekap application. This technical guidance activity took place in the Blorok Village Hall hall on January 25 2024 with the number of KPPS participants being 56 people. This activity took place in an orderly, safe and smooth manner. Participants can properly understand the technical instructions for voting and counting votes in the 2024 general election by filling in the C-Results form.